(untitled) (Palíndromo, 2022)
This article presents a systematic bibliographical review on the discussions about creation processes that explore textile art through poetics intertwined with craftsmanship in Brazilian Postgraduate productions. In order to analyze the most recent discussions, the mapping was limited to the time frame between 2010 and 2020 and to the space of the Digital Library of Theses and Dissertations (BDTD) of the Brazilian Institute of Science and Technology (IBICT). Through the advanced search with crossing of key descriptors, it was possible to collect data from six documents that approach the investigated questions. The result of the mapping presented the clipping of research, textile art and visual poetics, as a promising field for further research on the subject, from different perspectives.